Molecular hydrogen as an adjuvant therapy may be associated with increased oxygen saturation and improved exercise tolerance in a COVID‐19 patient - Ram B. Singh (Wiley, 2021)
Abstract Administration of molecular hydrogen dissolved in water to patient with COVID‐19‐like symptoms may improve oxygen levels and exercise capacity.